TAMAN RAKYAT DI KOTA UNAAHA KABUPATEN KONAWE DENGAN PENDEKATAN ARSITEKTUR EKOLOGI - Putra, Ardiansyah; Nahdatunnisa; Andi Al-Mustagfir Syah (Fakultas Teknik, Universitas Muhammadiyah Kendari, 2025)
The design of the people's Park in Unaaha City, Konawe Regency, aims to provide a recreational public space that reflects local character and supports ecological balance, Applying an ekoloogical architecture approach, the park is envisioned as a healthy, aesthetic, and inclusive green space that enhances environmental quality and community well-being. The design process includes site potential analysis based on local spatial planning, accessibility assessment, and the application of ecological principles such as energy efficiency, sustainability, and user comfort. The scope focuses on creating an environmentally friendly public tourism destination that integrates social, cultural, and ecological values. The results show that, with its strategic location and ecological concept, the park has the potential to become a new city icon, boost tourism growth, and improve the community’s quality of life, aims to design a people's park based on ecological architecture in Unaaha City.